Review on gas-solid fluidized bed particle solar receivers applied in concentrated solar applications: Materials, configurations and methodologies. (October 2021) - Jiang, Kaijun; Du, Xiaoze; Zhang, Qiang; Kong, Yanqiang; Xu, Chao; Ju, Xing
Abstract: The particle solar receivers (PSRs) have attracted widespread attention because of their high-temperature absorption and thermal energy storage functions. Among varieties of receivers, fluidized bed particle solar receivers (FB-PSRs), which based upon gas-solid fluidized bed technologies, have excellent heat transfer performance and high thermal efficiency. FB-PSRs provide new opportunities for the development of next-generation concentrated solar power (CSP) stations. As a good reactor, FB-PSRs can also be applied in the concentrated solar thermochemistry industry such as particulate reactive process, water splitting, calcination and so on. In this paper, different types of FB-PSRs for concentrated solar applications have been comprehensively reviewed, including upflow bubbling fluidized bed solar receiver, linear particle solar receiver, countercurrent fluidized bed particle receiver, autothermal fluidized bed solar receiver and solar air receiver based on particle heat collection. Furthermore, both the merits, limitations and applications of different FB-PSRs are discussed. As one of the most mature technology, the feasibility of the upflow bubbling fluidized bed solar receiver is proved by on-sun testing with outlet particle temperature exceeding 750 °C and high wall-to-bed HTC exceeding 1000 W/m 2 ∙K, and may have the potential to drive a megawatt-scale CSP plant when the problem of slugs solved. The properties of particles affect the FB-PSR performance and particles need to be properly selected. Moreover, the research methodology that refers to FB-PSRs is summarized. This review thus serves as a useful reference for the design and research of high-temperature particle solar receivers based on gas-solid fluidized technologies. Highlights: Provides an up-to-date comprehensive overview of particle receivers/reactors based on fluidized bed technology. Reviews and discusses previous progress on materials' selection principles. Analyses the research status and characteristics of particle receivers/reactors. Assesses merits, constraints, applications, and prospects of particle receivers/reactors. Summarizes research methods of gas-solid fluidized bed technology applied in CSP.